1994
DOI: 10.1111/j.1440-1827.1994.tb01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign schwannoma of the esophagus: Report of two cases with immunohistochemical and ultrastructural studies

Abstract: Two cases of benign schwannoma of the esophagus are presented. The tumors were found in the thoracic esophagus of women of 56 and 64 years of age, respectively, who had complained of dysphagia and back pain. Tumorectomies were performed and the tumors were found to be located within the esophageal wall arising from the muscularis propria. The tumors were examined immunohistochemically and ultrastructurally. These tumors were identical in gross, histological and electron microscopic features. Grossly, the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Esophageal schwannoma is rare, with only 19 reported cases. [1][2][3][4][5] Schwannomas tend to arise during the fourth to fifth decades of life and are more common in women and in blacks. [1][2][3] These tumors have been classified as a subset of gastrointestinal stromal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal schwannoma is rare, with only 19 reported cases. [1][2][3][4][5] Schwannomas tend to arise during the fourth to fifth decades of life and are more common in women and in blacks. [1][2][3] These tumors have been classified as a subset of gastrointestinal stromal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4 Tumors in the esophagus most often appear in the cervical segment. 5 Management of esophageal schwannomas remains controversial owing to the lack of knowledge of the natural history of the disease and the difficulty in distinguishing these masses from other types of submucosal tumors before surgery. In their review of 19 published cases, Murase et al 2 reported that none had had a preoperative diagnosis of schwannoma.…”
Section: Discussionmentioning
confidence: 99%
“…Benign schwannoma of the esophagus has been described in five cases in four reports in the English literature. [4][5][6][7] Seven cases were reported in Japanese and three cases were diagnosed by immunohistochemical studies up until 1997. [15][16][17] These lesions all ranged from 0.5 to 14 cm in greatest diameter.…”
Section: Discussionmentioning
confidence: 99%
“…18 Positive immunoreactivity for S-100 protein, NSE, Lew 7, laminin, and GFAP indicate the Schwann nature of the tumor. 1,2,7,11,12 Benign schwannomas of the digestive tract are thought to have originated from neuronsupporting cells in the myenteric plexus or site-specific modified Schwann cells. 2 On the other hand, no smooth muscle markers, such as actin and desmine, were positive in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical examination of the tumor cells is considered the optimal diagnostic tool for this type of tumor (14). Schwannomas usually exhibit positive reactivity for S-100, vimentin and glial fibrillary acidic protein, and no reactivity for CD117, CD34, actin or cytokeratins, which appear more typically in GISTs, gastrointestinal autonomic tumors or muscle tumors (15,16).…”
Section: Discussionmentioning
confidence: 99%